The Influence of Digital Media on Creative Writing - Fidela Shaumi Suryadi; Deni Suswanto (Jurnal Syntax Admiration, 2024)
This study examines the impact of digital media on creative writing practices. Through a review of existing literature and analysis of relevant case studies, the study explores how digital platforms such as online blogs, social media, and interactive storytelling websites have reshaped the creative writing landscape. The findings reveal that digital media offer writers new tools and opportunities for experimentation, including multimedia elements and real-time audience engagement. However, challenges such as digital literacy and concerns about content authenticity also emerge. Overall, digital media have both positive and negative influences on creative writing, highlighting the need for further research and adaptation in the evolving digital environment.